Post Mastectomy Pain is No Longer Nightmare - Alaa Ali M. Elzohry; Mohammed Farghaly Abd Elhamed; Mohammed Hesien Mahran (Journal of Family Medicine, 2018)
Background PMPS nowadays is common due to advances in both; diagnosis and treatment of cancer breast. Choosing proper treatments can improve the patients’ quality of life. Cancer breast is common and quite important disease and female in our family must be aware of it. Improvement of the diagnosis and treatment PMPS lead to increased patient’s satisfaction and decrease fear of cancer breast. Objective Discuss different methods for management of PMPS with less side effects, adequate analgesia, improvement of quality of life, and better patient satisfaction in the future. Methods Treatment approaches include both pharmacological interventions and non-pharmacological strategies. However, current treatments of the PMPS are near-optimal and prevention much better than treatment. Conclusion Continuous perioperative thoracic epidural Fentanyl–bupivacaine infusion was much better in pain relief, less sedating effect and shorter duration of hospital and ICU stay than continuous perioperative entanyl intravenous infusion in patients undergoing major upper gastrointestinal cancer surgery.
Keywords: PMPS